The Effect of TQM on the Balanced Performance - Al-Khawaldeh, Khleef; Smadi, Majed (Jordan Journal of Business Administration, 2021)
Total Quality Management (TQM) has become a part of business thinking and a managerial paradigm in the last two decades. Business firms attempt to improve their competitiveness through improving their performance. The purpose of this study is to investigate whether this in fact the case. The effect of TQM on performance has been extensively analyzed by researchers, but this sort of research has usually been biased to financial performance measures, which are insufficient to measure and integrate all factors that are significant for the success of the firm. This study aimed to investigate the impact of TQM adoption on balanced performance as recently defined by the methodology of balanced scorecard and lagging factors of Baldrige Award (overall business results). To achieve this objective, a sample of (300) firms from Dubai manufacturing firms were selected to fill the developed questionnaire. About 42% of the distributed questionnaires were collected and subjected to statistical analysis. Results revealed that 71.5% of the variation in firms’ balanced performance (as measured by financial performance, operational performance, customer satisfaction and employee satisfaction) is due to the application of all TQM constructs. These results support the proposition that TQM implementation leads to better performance in the manufacturing sector.